Climate Toolkit A Resource Manual for Science and Action - Granshaw, Frank (Open textbook library., 2021)
The Climate Toolkit is a resource manual designed to help the reader navigate the complex and perplexing issue of climate change by providing tools and strategies to explore the underlying science. As such it contains a collection of activities that make use of readily available on-line resources developed by research groups and public agencies. These include web-based climate models, climate data archives, interactive atlases, policy papers, and “solution” catalogs. Unlike a standard textbook, it is designed to help readers do their own climate research and devise their own perspective rather than providing them with a script to assimilate and repeat. The activities in the manual are divided into five sections that include weather and climate basics, present climate impacts, past climate change, future change and impacts, and strategies for climate mitigation and adaptation. These are followed by three appendices which contain information about the on-line tools used in the activities in this manual; a catalog of on-line and print resources produced by research groups, government agencies, and community groups involved in climate and sustainability work; and background on the history and key players in the international climate negotiation process. Though originally aimed at undergraduate non-science majors, the manual has been broadened for a wider audience in non-academic settings like community groups, service organizations, workplace study groups, and faith communities.